2009
DOI: 10.1007/s10329-009-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

Of how much concern are the ‘least concern’ species? Distribution and conservation status of bonnet macaques, rhesus macaques and Hanuman langurs in Karnataka, India

Abstract: We assessed the distribution and conservation status of bonnet macaques (Macaca radiata), rhesus macaques (Macaca mulatta) and Hanuman langurs (Semnopithecus entellus) in the state of Karnataka, India. Karnataka is situated in southwest India with an area of 191,791 km(2). A total of 9697 km of vehicular survey was made from November 2001 to July 2004. We also visited 107 temples/tourist spots to determine the presence of primates. Bonnet macaques and Hanuman langurs were widely distributed, whereas rhesus mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…In the present study, the encounter rate of 0.05 groups/ km is comparable to the encounter rate of 0.021 groups/km found in Karnataka (Kumara et al 2010a). Although bonnet macaques are usually found at higher densities in marginal and unprotected habitats (Kumara et al 2010b), in our study, the group encounter rate was higher (though not statistically bonnet macaque individuals was highest in forests, whereas in Karnataka, the number of bonnet macaques sighted was highest in areas of human habitation and lowest in forests.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In the present study, the encounter rate of 0.05 groups/ km is comparable to the encounter rate of 0.021 groups/km found in Karnataka (Kumara et al 2010a). Although bonnet macaques are usually found at higher densities in marginal and unprotected habitats (Kumara et al 2010b), in our study, the group encounter rate was higher (though not statistically bonnet macaque individuals was highest in forests, whereas in Karnataka, the number of bonnet macaques sighted was highest in areas of human habitation and lowest in forests.…”
Section: Discussionsupporting
confidence: 66%
“…Unfortunately decline of bonnet macaque populations in southern India. In the neighboring state of Karnataka, Kumara et al (2010a) noted that nearly 91% of the coastal populations of M. radiata have been extirpated. Secondary information collected during the course of our study also indicated that bonnet macaques have long been extirpated from coastal towns such as Siolim.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A great number of species underrepresented by PAs were considered of Least Concern, according to IUCN criteria (IUCN 2010). However, strong population declines have also been reported for species classified as of least concern in different parts of the world (del Hoyo et al 2003;Kumara et al 2010). In this sense, policy makers should also take into account these species when designing PA networks to ensure that their distribution and population flows are maintained across the RBMA.…”
Section: Discussionmentioning
confidence: 99%